"fokkol graad vi jou nie" [Fuck All Degree for You]: Black Afrikaans Poets, Critical University Studies, and Transcripting the Afrikaans University. - Staphorst, Luan (Journal of African Cultural Studies, 2023)
Against the backdrop of #Rhodesmustfall and calls for the decolonisation of the South African academy, #Afrikaansmustfall arose specifically targeting the continued use of Afrikaans as a language of teaching and learning. This article investigates the ways in which young, Black Afrikaans speakers – the often invisible members of the Afrikaans community – are critiquing and reimagining the hegemonic form of the Afrikaans language and university. The analysis centres on poems from the debut anthologies of Ashwin Arendse and Veronique Jephtas, namely Swatland (2021) and Soe Rond Ommie Bos (2021) – both of which are written in Kaaps, a non-standardised variant of Afrikaans. Critical university studies and James Scott's notion of transcripts are the central frames through which the article speculates as to what a future form of the Afrikaans university, namely the African-Afrikaans university, could look like. The new script for this university includes being anti-racist, anti-neoliberal, and affective – whilst a concretely broadened form of Afrikaans grounds it.